Ensemble Methods for Monitoring Enzyme Translocation along Single Stranded Nucleic Acids - Tomko, Eric J. (2010)
We review transient kinetic methods developed to study the mechanism of translocation of nucleic acid motor proteins. One useful stopped-flow fluorescence method monitors arrival of the translocase at the end of a fluorescently labeled nucleic acid. When conducted under single-round conditions the time courses can be analyzed quantitatively using n-step sequential models to determine the kinetic parameters for translocation (rate, kinetic step size and processivity). The assay and analysis discussed here can be used to study enzyme translocation along a linear lattice such as ssDNA or ssRNA. We outline the methods for experimental design and two approaches, along with their limitations, that can be used to analyze the time courses. Analysis of the full time courses using n-step sequential models always yields an accurate estimate of the translocation rate. An alternative semi-quantitative “time to peak” analysis yields accurate estimates of translocation rates only if the enzyme initiates translocation from a unique site on the nucleic acid. However, if initiation occurs at random sites along the nucleic acid, then the “time to peak” analysis can yield inaccurate estimates of even the rates of translocation depending on the values of other kinetic parameters, especially the rate of dissociation of the translocase. Thus, in those cases analysis of the full time course is needed to obtain accurate estimates of translocation rates.